1993
DOI: 10.1007/bf01316909
|View full text |Cite
|
Sign up to set email alerts
|

Possibility of reinfection after immunisation with RA 27/3 live attenuated rubella virus

Abstract: A serological study was carried out on 527 girls immunized with RA 27/3 rubella vaccine. Data from all scheduled serum samples over a 5-year follow-up were available for 102 vaccinees, 10 (9.8%) of whom showed evidence of reinfection during the 5th year after immunisation, a year in which there was a rubella outbreak in the Siena area (Italy). We examined in greater detail the serological responses of these vaccinees after reinfection and the consequent implications pertinent to the duration of the protective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
1

Year Published

1994
1994
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 10 publications
(11 reference statements)
0
13
0
1
Order By: Relevance
“…Furthermore, these methods only assess the humoral immune response without capturing the role of cellular immunity, which also plays a significant role in immunity to rubella infection. The observed decline in antibody levels over time [8,23] may be explained by the increased proportion of women relying solely on vaccine-induced immunity for protection. In a follow-up of rubella immunity in Finland [24], 100% of vaccinated individuals had detectable levels of rubella IgG (≥4 IU/mL) after 15-20 years, however only 64% had levels that were considered protective (>15 IU/mL).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, these methods only assess the humoral immune response without capturing the role of cellular immunity, which also plays a significant role in immunity to rubella infection. The observed decline in antibody levels over time [8,23] may be explained by the increased proportion of women relying solely on vaccine-induced immunity for protection. In a follow-up of rubella immunity in Finland [24], 100% of vaccinated individuals had detectable levels of rubella IgG (≥4 IU/mL) after 15-20 years, however only 64% had levels that were considered protective (>15 IU/mL).…”
Section: Discussionmentioning
confidence: 99%
“…The frequency of rubella virus re‐infection after vaccination may vary between 10% and 22%—a 10‐fold greater rate than naturally immune individuals with low rubella antibody levels [Cusi et al, 1993]. Re‐infections with rubella are usually subclinical; however, in the present study, all suspected re‐infection patients showed symptoms.…”
Section: Discussionmentioning
confidence: 53%
“…However, infections despite prior vaccination resulting in titer rises of preexisting antibody levels have been described [5,14,24,[36][37][38][39]. However, infections despite prior vaccination resulting in titer rises of preexisting antibody levels have been described [5,14,24,[36][37][38][39].…”
Section: Discussionmentioning
confidence: 99%
“…The US Armed Forces have been asking recruits for their vaccination records since 1980 and updating them as needed, thereby reducing the incidence of vaccine preventable diseases [39,42]. In a worst case scenario the success of a mission could be endangered if soldiers in key positions are affected.…”
Section: Discussionmentioning
confidence: 99%